Investigation of the risk factors to predict cytokine release syndrome in relapsed or refractory B-cell acute lymphoblastic leukemia patients receiving IL-6 knocking down anti-CD19 chimeric antigen receptor T-cell therapy - Gong, Wen-Jie; Qiu, Yan; Li, Ming-Hao; Chen, Li-Yun; Li, Yan-Yan; Yu, Jing-Qiu; Kang, Li-Qing; Sun, Ai-Ning; Wu, De-Pei; Yu, Lei; Xue, Sheng-Li (Frontiers in Immunology, 2022)
CD19 chimeric antigen receptor-T (CAR-T) cell therapy has achieved remarkable results in patients with relapsed or refractory B-cell acute lymphoblastic leukemia (r/r B-ALL). However, the cytokine release syndrome (CRS) was presented in a majority of patients as a common toxicity and severe CRS (sCRS) characterized by the sharp rise in interleukin-6 (IL-6) could be life-threatening. We conducted a phase II clinical trial of ssCAR-T-19 cells, anti-CD19 CAR-T cells with shRNA targeting IL-6, in 61 patients with r/r B-ALL. This trial was registered at www.clinicaltrials.gov as #NCT03275493. 52 patients achieved CR while 9 patients were considered NR. Median duration of response (DOR) and overall survival (OS) were not reached (>50 months). CRS developed in 81.97% of patients, including 54.10% with grade 1 to 2 (grade 1, 31.15%; grade 2, 22.95%) and 27.87% with grade 3 to 4 (grade 3, 26.23%; grade 4, 1.64%). sCRS occurred earlier than mild CRS (mCRS). Multivariable analysis of baseline characteristics identified high bone marrow disease burden and poor genetic risk before infusion as independent risk factors of sCRS. After infusion, patients with sCRS exhibited larger expansion of ssCAR-T- 19 cells, higher peak levels of IL-6, IL-10 and IFN-γ, and suffered more severe hematological and non-hematological toxicities when compared to those with mCRS.